Theoretical and methodological approaches to the problem of student’s health in the algorithm of recreational activities - Viacheslav Zaytzev; Krzysztof Prusik; Svitlana Manucharyan (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The aim of the study is theoretical and methodological approaches to the problem of student’s health in the algorithm of recreational activities.